Many children, many blessings: Reinterpreting Psalm 127:5 in the Nigerian context - Ademiluka, Solomon O. (Journal for Semitics, 2024)
The idea of “many children, many blessings” in Ps 127:5 resonates with African traditional belief systems. However, in contemporary Nigeria, modernisation has introduced inescapable variables that make large families undesirable. In spite of this, many Nigerians still produce many children, apparently relying on the traditional belief that God determines one’s number of children, and possibly also on Ps 127:5. Applying the historical-critical and descriptive methods, the article assessed the relevance of Ps 127:5 in contemporary Nigeria and found that the text reflects the ancient Israelite context wherein parents depended on the number of their children in socio-economic terms, a situation which also resonates with the premodern African context. The modern Nigerian context, however, brought about changes in the pattern of parent-child interdependence such that now even peasant parents have to send their children to school and do all the manual work alone. In view of the high rate of unemployment, even many university graduates still have to depend on their parents. With this transition, large families come with implications such as hunger, poor health, and inadequate or lack of Western education for the children. Moreover, raising large families now has to contend with global issues such as overpopulation and family planning. To this end, a pastoral application of Ps 127:5 in Nigeria now has to respond to issues that come with large families.
paid